Pt-Ni/WC Alloy Nanorods Arrays as ORR Catalyst for PEM Fuel Cells. (24th August 2017) - Begum, Mahbuba; Yurukcu, Mesut; Yurtsever, Fatma; Ergul, Busra; Kariuki, Nancy; Myers, Deborah J; Karabacak, Tansel
Abstract : Polymer electrolyte membrane fuel cells (PEMFCs) among the other types of fuel cell technology are attractive power sources, especially for electric vehicle applications. While significant progress and plausible prospects of PEMFCs have been achieved, there are still some challenges related to the performance, durability, and cost that need to be overcome to make them economically viable for widespread commercialization. Our strategy is to develop thin films of high-active and stable catalyst coated on vertically aligned nanorod arrays of conductive and stable support. In this work, we fabricated tungsten carbide (WC) nanorods as support and coated them with a platinum-nickel (Pt-Ni) alloy shell denoted as Pt-Ni/WC catalysts. The Pt-Ni/WC nanorods were deposited on glassy carbon disks as well as on silicon substrates for evaluation of their electrocatalytic oxygen reduction reaction (ORR) activity and physical properties. Cyclic voltammetry experiments using rotating disk electrode were performed in perchloric acid (0.1 M HClO4 ) electrolyte at room temperature to characterize the ORR activity and stability of Pt-Ni/WC nanorods catalysts. Scanning electron microscopy and X-ray diffraction techniques were utilized to study the morphology and crystallographic properties, respectively.